The influence of context on the temporal interpretation of verbs in Mandarin Chinese: Challenges for Spanish speakers (Sinología hispánica. China Studies Review, 2025)
This study examines the role of context in the temporal interpretation of verbs in Mandarin Chinese from the perspective of Spanish speakers. Unlike Spanish, where tense is marked through verbal inflections, Chinese relies on aspectual particles such as “了 (le)”, “过 (guo)”, and “着 (zhe)”, along with temporal adverbs, to situate actions within the timeline. However, understanding these markers heavily depends on linguistic, cultural, and situational factors. Since Spanish explicitly expresses temporality through verbal morphology, this study emphasizes the need for a contrastive approach in Mandarin teaching, focusing on pragmatic and contextual strategies. The specific challenges that Spanish speakers face when interpreting and translating the temporal nuances of Chinese are examined, highlighting the structural differences between the two systems. The findings suggest that effective communication requires a broader perspective on context, integrating not only discourse structure but also pragmatic cues and sociocultural conventions. In this regard, pedagogical strategies specifically designed for Spanish speakers are proposed, aiming to enhance their comprehension and production of temporal expressions in Chinese.